On Learning, Playfulness, and Becoming Human - An, Christopher Joseph G (Archīum Ateneo, 2018)
This essay aims to develop the so-called ‘transformational view’ of human development (advocated by McDowell and Bakhurst) by advancing a play-based model of learning. I first consider challenges to this view posed by Luntley and Rödl who argue that the learning encounter must presuppose some rational faculty already present in the prelinguistic child. Rödl in particular considers joint attentional episodes in which child and adult attend to objects in their environment together as signifying a uniquely rational consciousness active in the human child. I however argue on phenomenological grounds that this intellectualist treatment is implausible and unconvincing. I propose a play-centered treatment (inspired primarily from Huizinga) that is more sensitive to the life of the child. This perspective of play I maintain scaffolds a shared normative space which enables self-conscious; responsive; and intelligible thought and action. This account motivates what I call a participatory play model of learning which is constitutively non-intellectual but is nonetheless intelligent. It is non-intellectual because it emphasizes building co-reactive relationships and participation in shared cultural practices. But it is also intelligent because it makes possible a distinctively human mode of understanding grounded on an interactive; relational; and imaginatively reflexive engagement with the world.